Hydrological Analysis for Inflow Forecasting into Temengor Dam - Najid M.I.; Sidek L.M.; Hidayah B.; Roseli Z.A. (Institute of Physics Publishing, 2023)
Artificial intelligence; Calibration; Catchments; Dams; Decision support systems; Disasters; Flood control; Floods; Forecasting; Reservoirs (water); Runoff; Travel time; Decision supports; Flood hydrographs; Forecasting modeling; Hydrological analysis; Natural disasters; Operational decision support; Rainfall contributions; Rainfall distribution; Rain; calibration; catchment; dam; decision support system; flood; flood control; flood forecasting; hydrograph; hydrological modeling; inflow; monsoon; peak discharge; prediction; rainfall; reservoir; warning system; Malaysia; Perak; Perak River; Temenggor Reservoir; West Malaysia